The psychological mechanisms through which digital content marketing by online influencers affects customer loyalty: evidence from multiple countries - Zhang, Qin; Abdullah, Firdaus (Frontiers in Communication, 2025)
IntroductionThis study examines the impact of digital content marketing on customer loyalty in the context of a rapidly evolving consumer environment marked by rising national income levels and shifting consumption patterns. Drawing on relationship marketing theory (RMT) and self-determination theory (SDT), the study explores how emotional attachment and emotional commitment moderate the relationship between digital content marketing and customer loyalty. By investigating emotional mechanisms in digital content marketing, this study expands the explanatory power of RMT in digital contexts and enriches the application of SDT in consumers’ emotional motivations and loyalty.MethodsUsing a quantitative research approach, based on multinational sample mainly from Asia (996 valid responses), the study employs partial least squares structural equation modelling (PLS-SEM) to analyse the proposed model.ResultsThe findings reveal that high-quality digital content marketing significantly enhances customer loyalty, and this relationship is strengthened by both emotional attachment and emotional commitment.DiscussionThis study innovatively integrates emotional drivers into digital marketing, addressing the existing gap in exploring emotional mechanisms in this field. It not only enriches theoretical research at the intersection of digital marketing and relationship marketing but also offers practical insights for marketing managers and digital strategists, particularly in highly dynamic and emotionally driven consumer markets. This paper advances the understanding of how emotional mechanisms interact with digital marketing strategies to foster long-term customer relationships, offering implications for both theory and practice. Although the sample mainly from Asia, a leading region for digital marketing and e-commerce, the findings provide valuable insights into the emotional impact of digital content marketing within a global context.